ETHICAL LEADERSHIP: CONCEPTUALIZATION AND MEASUREMENT - Madyaning Krisharyuli; Fathul Himam; Zulmi Ramdani (Journal of Leadership in Organizations, 2020)
This study aims to find out and build theory and interviews with making a scale and begin to measure the scale of ethical leadership. Not many measurements make the scale of ethical leadership by involving indigenous perspectives in its construction, so it becomes important to scale ethical leadership. Completed research method by using mixed methods for 195 leaders as respondents in the Yogyakarta City Government. Five leaders as respondents were interviewed using feno-grounded theory, 30 respondents in the step of trying out the scale, and 161 respondents for ethical research instruments. The results of the study show that the concept is also by the leader for things such as honesty, fairness, and openness in accordance with applicable rules. There are three factors in the scale of Ethical Leadership, namely Integrity, Professionalism, and Personal Development, which produces reliability r=0.843 with the number of items 24. The range of values of the loading factor between 0.306 to 0.719 shows the scale of ethical leadership, including valid and reliable able to measure the tendency of ethical leadership. Thus, the ethical leadership scales psychologically appropriate to be used to see the profile of the individual who acts as leaders.